2014
DOI: 10.2967/jnmt.113.131581
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Octreotide Uptake in the Uterus and a Subserosal Myoma Mimicking Tumoral Masses

Abstract: The diagnostic usefulness of somatostatin receptor scintigraphy in the localization of tumors has been evaluated in several studies. Here, we present the case of a patient with a subserosal myoma diagnosed by 99m Tc-labeled octreotide acetate scintigraphy. Oval and ring-shaped areas of hyperactivity in the pelvis were confirmed on MR imaging to be the uterus and a subserosal myoma. The presented case indicates that somatostatin receptors may be present in the uterus and in leiomyomas, especially in young women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…After surgical removal, the patient's symptoms resolved and significant clinical improvement was achieved. Pirayesh et al 25 reported a case of a neuroendocrine tumor in a 30-year-old woman in which 99m Tc-octreotide acetate scintigraphy revealed uptake in the uterus and a subserosal myoma mimicking tumoral masses. Tc-TRODAT-1 Production.…”
Section: Local Clinical Evaluations Beiki Et Al 21 Evaluated This Nementioning
confidence: 99%
“…After surgical removal, the patient's symptoms resolved and significant clinical improvement was achieved. Pirayesh et al 25 reported a case of a neuroendocrine tumor in a 30-year-old woman in which 99m Tc-octreotide acetate scintigraphy revealed uptake in the uterus and a subserosal myoma mimicking tumoral masses. Tc-TRODAT-1 Production.…”
Section: Local Clinical Evaluations Beiki Et Al 21 Evaluated This Nementioning
confidence: 99%
“…According to Kagna et al, 11 the 68 Ga-DOTA-NOC uptake was not associated with any NET in 72% of cases, and the uterus was the third most common location of tracer accumulation. Furthermore, the benign uptake of DOTATATE tracer by uterine fibroid has been described in few studies, attributing to the aberrant expression of somatostatin receptors or hypermetabolism of the fibroid tissue 4,12,13 …”
mentioning
confidence: 99%
“…Furthermore, the benign uptake of DOTATATE tracer by uterine fibroid has been described in few studies, attributing to the aberrant expression of somatostatin receptors or hypermetabolism of the fibroid tissue. 4,12,13…”
mentioning
confidence: 99%
“…SSTR expression in uterine leiomyoma, although documented in few case reports, is a rare event. [1][2][3][4][5] It has been observed in animal studies that inflammation of the myometrium increases SSTR-2 and SSTR-5 expression. 6 This case demonstrates very high SSTR expression; unlike previous cases reported in literature, this may occur in the presence of any ongoing degeneration.…”
mentioning
confidence: 99%
“…Section examined ( E and F ) from the intramural fibroid showed a smooth muscle tumor arranged in intersecting fascicular pattern ( E , hematoxylin-eosin, ×100; F , hematoxylin-eosin, ×200). SSTR expression in uterine leiomyoma, although documented in few case reports, is a rare event 1–5 . It has been observed in animal studies that inflammation of the myometrium increases SSTR-2 and SSTR-5 expression 6 .…”
mentioning
confidence: 99%